2017
DOI: 10.3847/1538-4357/aa901f
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Vlasov–Poisson Simulations with High-order Monotonicity- and Positivity-preserving Schemes

Abstract: We develop new numerical schemes for Vlasov-Poisson equations with high-order accuracy. Our methods are based on a spatially monotonicity-preserving (MP) scheme and are modified suitably so that positivity of the distribution function is also preserved. We adopt an efficient semi-Lagrangian time integration scheme that is more accurate and computationally less expensive than the threestage TVD Runge-Kutta integration. We apply our spatially fifth-and seventh-order schemes to a suite of simulations of collision… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…It is shown that the spatial and velocity resolutions should be adapted together rather than independently for optimal efficiency. This contributes to the ongoing discussion [4][5][6][7], of splitting vs non-splitting methods for mesh adaptation in phase space.…”
Section: Editorial On the Research Topic Adaptive Kinetic-fluid Modelmentioning
confidence: 90%
“…It is shown that the spatial and velocity resolutions should be adapted together rather than independently for optimal efficiency. This contributes to the ongoing discussion [4][5][6][7], of splitting vs non-splitting methods for mesh adaptation in phase space.…”
Section: Editorial On the Research Topic Adaptive Kinetic-fluid Modelmentioning
confidence: 90%
“…In order to reveal how faithfully the SCF simulations shown here can follow the true evolution, the most desirable approach may be a comparison of the simulations with the SCF code to those with a six-dimensional phase-space code developed by Yoshikawa et al (2013), which has been touched up by Tanaka et al (2017), or with that based on a moving adaptive simplicial tessellation method devised by Sousbie & Colombi (2016), since no gravitational softening is included in these codes. In fact, Yoshikawa et al (2013) have presented a sample simulation of merging two identical King spheres.…”
Section: Effects Of Softening Lengthmentioning
confidence: 99%
“…However, this limiter has limitation of Courant-Friedrichs-Lewy (CFL) condition. It has been applied recently to the Semi-Lagrangian method and for the Vlasov-Poisson system [49]. Note also that an extension work of [48] has been made [21] to give more relaxation space.…”
Section: Introductionmentioning
confidence: 99%